Preparation of ?-Caprolactone/Fe3O4 Magnetic Nanocomposite and Its Application to the Remazol Brilliant Violet 5R Dye Adsorption from Wastewaters by Using RSM - Pekdemir, Mustafa Ersin; Tanyol, Mehtap; Torgut, Gulben (Springer, 2022)
In this study, poly (epsilon-caprolactone)/Fe3O4 magnetic nanocomposite (PCL/Fe3O4 MNC) was synthesized by ring-opening polymerization. Then, PCL/Fe3O4 MNC was used as a novel adsorbent to remove remazol brilliant violet 5R (RBV 5R) from the aqueous media. The effects of PCL/Fe3O4 MNC dosage, process time, and initial RBV 5R concentration on the removal of RBV 5R were studied using the central composite design (CCD) method. The adsorption process was optimized using the response surface methodology, and the optimum conditions were defined. Optimum RBV 5R removal of 95.40% was obtained at a contact time of 167.98 min, PCL/Fe3O4 MNC dosage of 0.40 g, and RBV 5R concentration of 7.18 mg L-1. The process was also designed using the adsorption kinetic models and isotherm. The experimental data of RBV 5R adsorption on PCL/Fe3O4 MNC followed the Langmuir isotherm and pseudo-second-order kinetic models than the other models. Morphological and chemical properties of the adsorbent-adsorbate system indicated the high adsorption yield of RBV 5R on PCL/Fe3O4 MNC was achieved. The structural characteristics of the PCL/Fe3O4 MNC were analyzed by Fourier-transform infrared, attenuated total-reflectance (ATR), and X-ray diffraction. ATR tests showed that no significant change in chemical bond is found in PCL/Fe3O4 MNC before and after the adsorption process. The morphology of composites was investigated by scanning electron microscopy. A vibrating sample magnetometer (VSM) was used for the measurement of the magnetic property. Thermal analysis of MNC was studied using thermogravimetric analysis and differential scanning calorimetry instruments.
Keywords: Magnetic nanocomposite; Adsorption; Response surface methodology; Remazol brilliant violet 5R; CCD